Loss of NFIX transcription factor biases postnatal neural stem/progenitor cells toward oligodendrogenesis - Zhou, Bo; Osinski, Jason M.; Mateo, Juan L.; Martynoga, Ben; Sim, Fraser J.; Campbell, Christine E.; Guillemot, Francois; Piper, Michael; Gronostajski, Richard M. (Stem Cells and Development, 2015)
Murine postnatal neural stem cells (NSCs) give rise to neurons, astrocytes, or oligodendrocytes (OLs); however, our knowledge of the genes that control this lineage specification is incomplete. In this study, we show that nuclear factor I X (NFIX), a transcription factor known to regulate NSC quiescence, also suppresses oligodendrogenesis (ODG) from NSCs. Immunostaining reveals little or no expression of NFIX in OL lineage cells both in vivo and in vitro. Loss of NFIX from subventricular zone (SVZ) NSCs results in enhanced ODG both in vivo and in vitro, while forced expression of NFIX blocks NSC differentiation into OLs in vitro. RNA-seq analysis shows that genes previously shown to be differentially expressed in OL progenitors are significantly enriched in RNA from Nfix−/− versus wild-type NSCs. These data indicate that NFIX influences the lineage specification of postnatal SVZ NSCs, specifically suppressing ODG.
Gesehen am 04.08.2020